Investigating the Feasibility of Photostimulation for the Development of a Low Energy-Spread Electron Microscope Source. - Quigley, Frances Eileen (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
Electron microscopes use fast-moving electrons as illumination to generate high resolution images down to the atomic scale. They are a valuable tool in various research fields, from palaeontology to material science. Low voltage imaging in particular is becoming an increasingly popular technique due to its many applications. These include imaging materials sensitive to knock-on damage, decreasing charging effects on insulating samples and improving surface sensitive imaging. However, the illumination of the beam during low voltage imaging is limited by chromatic aberration, the premature focus of lower energy electrons on the optic axis compared to higher energy electrons. Decreasing the electron's energy-spread (Delta E) is one route to reducing the chromatic defocus blur. This can be achieved by installing an electron monochromator or upgrading to a lower energy-spread electron source, such as a cold field emission gun (FEG) (Delta E ~ 0.3eV ). These however can be expensive options, out of the reach of less funded laboratories. This thesis presents an alternative solution, exploiting the photoelectric effect where photons are used to stimulate the direct release of low energy-spread electrons from the low workfunction material Lanthanum Hexaboride (LaB6). Using fibre optics and a UV laser diode, a prototype has been retrofitted onto the existing thermionic LaB6 electron gun in a ZEISS EVO SEM, and results from this will be presented. Based on previous literature, the photoelectrons produced from this retrofitted emitter are predicted to have an energy-spread as low as Delta Ee=0.37 +/- 0.04eV. Images generated from this photoelectron emitter will be shown, and the optimisation of the developed apparatus to increase its photoelectron current will be outlined. Finally, the semi-permanent installation of this novel photoelectron emitter will be characterised with its resolution and brightness compared to other thermionic electron sources evaluated. While SEM images were successfully captured with this photoemitter, some further performance improvements would be needed before it is practically useful in low voltage imaging. Therefore, solutions to upgrade the emitter will also be outlined alongside some alternative uses for the source, including beam modulation and time-resolved SEM imaging. This prototype will hopefully lay the foundation for increasing the sustainability of existing microscopes, extending their lifetime by potentially increasing their functionality and performance.
APPROVED
Keywords: electron gun; low-voltage imaging; photoelectric effect; scanning electron microscope (SEM); UV laser diode; chromatic aberration; 3D Printing